Impact of Job Mutations on Auditor Performance (Study at the Kendari Inspectorate Office) - Tuti, Tuti Dharmawati; Ika Maya Sari; Safaruddin; Satira Yusuf4 (CV. Inara, 2021)
This research is motivated by the less than optimal performance of auditors at the Kendari Inspectorate Office. This study aims to determine the impact of work mutations on the performance of auditors at the Kendari City Inspectorate. The population in this study were all auditors of the Kendari City Inspectorate, which amounted to 14 employees, because the population in this study was relatively small and less than 30 people so that all members of the population were used as research samples or often known as saturated samples. The data collection technique was done by distributing questionnaires. The questionnaire used has been tested for validity and reliability. The data analysis technique used is simple linear regression analysis, namely t-test with the help of Statistical Package For Social Science (SPSS) version 21. The results of this study indicate that work mutations have a positive and significant impact on auditor performance at the Kendari City Inspectorate. Job mutations can be a motivation to improve auditor performance. Despite the pressure, the auditor was able to maintain its performance..